BINDING FORCE OF CONSTITUTIONAL REVIEW DECISION OF CONSTITUTIONAL COURT TOWARD SUPREME COURT - Rian Van Frits Kapitan (Faculty of Law, Universitas Jenderal Soedirman, 2016)
The Supreme Court decision which sentenced dr. Bambang suprapto.Sp.M.Surg. using article 76 of Law No 29 Year 2004 on the Practice of Medicine which had been annulled by the Constitutional Court has proved that the Supreme Court has put aside constitutional court's decision on constitutional review. This paper attempts to justify that at any reason, Constitutional Review decision of Constitutional Court still has binding force on the Supreme Court. It is based on four perspectives: 1. Historical perspective 2. Protected object perspective 3. Functional perspective, and 4. Normative perspective.Keywords: Binding Force, Constitutional Review, Constitutional Court, Supreme Court.